(untitled) (Praxis Educativa, 2025)
The work addresses the pedagogical implications for professional training in Social Work. Through an exercise called "collaborative autoethnographies," care is examined as an object of reflection and intervention. Drawing from the stories shared by the authors, it is revealed that care acts as an agent that takes on different forms depending on the circumstances experienced. Furthermore, the educational act within the university inherently involves a particular form of care. It is suggested that care adopts various guises and that identifying these is essential to avoid arbitrary practices from a professional perspective. This requires an ethical skill to discern its concrete forms. Keywords: educational act, collaborative autoethnographies, care, ethics of care, pedagogical derivations